Changes in breaststroke techniques under different speed conditions - Bober, T.; Czabanski, B. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
Training in different sport events has the realization of a definite set of aims. Generally, these purposes can be divided into tasks for developing skill, technique, or tactics. However, these elements are interdependent and each task, although it has a specific purpose, will indirectly influence the other aspects of the competitor's preparation. This is caused by the motoric nature of man, who realizes the aims of his activity by using a definite movement form which is consistent with his physical skill. Similarly, in swimming, training programs contain various degrees of emphasis upon skill, speed, strength, and endurance. It is known that swimming under different speed conditions causes changes in movement frequency (East, 1970). However, it can be expected that changes also occur in the technique of movement, especially in rhythm of the swimming cycle. In this study an attempt was made to characterize the interdependence of the breaststroke technique and the speed of swimming. It is hoped that the awareness of the side effects of the exercises utilized by coaches may improve the effectiveness of the teaching and coaching process.